Inside Bridgerton - Rhimes, Shonda; Beers, Betsy (Marysue Rucci Books/Scribner, 2022)
The smart, saucy, and official, full-colour, behind-the-scenes look at Netflix's Bridgerton. Featuring exclusive material from co-creators Shonda Rhimes and Betsy Beers and photos and interviews with cast and crew.